1989
DOI: 10.1111/j.1600-079x.1989.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Effects of Melatonin on Prolactin Cell Function in Male and Female Syrian Hamsters

Abstract: The purpose of this study was to determine and compare the effects of chronic melatonin treatment in vivo on several aspects of prolactin (PRL) cell activity (PRL synthesis, storage, and release) in vitro in male and female Syrian hamsters. Adult male and female hamsters were maintained on long photoperiod and treated with daily late afternoon injections of melatonin (25 micrograms) or vehicle for 11 weeks. Melatonin treatment resulted in an 85% and 65% decrease in serum PRL levels in male and female hamsters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Animal studies indicate that melatonin can modify the firing frequency of the hypothalamic gonadotropin-releasing hormone pulse generator, thereby affecting the release of gonadotropins (luteinizing hormone and follicle-stimulating hormone) from the pituitary (10-13) and stimulating testicular testosterone or ovarian estrogen production and release (14,15). Animal studies have also shown that melatonin can inhibit luteinizing hormone-induced testosterone production in rats (16)(17)(18), inhibits prolactin cell activity in male and female hamsters (19), and suppresses several aspects of reproductive physiology in male hamsters (20). Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…Animal studies indicate that melatonin can modify the firing frequency of the hypothalamic gonadotropin-releasing hormone pulse generator, thereby affecting the release of gonadotropins (luteinizing hormone and follicle-stimulating hormone) from the pituitary (10-13) and stimulating testicular testosterone or ovarian estrogen production and release (14,15). Animal studies have also shown that melatonin can inhibit luteinizing hormone-induced testosterone production in rats (16)(17)(18), inhibits prolactin cell activity in male and female hamsters (19), and suppresses several aspects of reproductive physiology in male hamsters (20). Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…by daily collection of vaginal smears). In the Syrian hamster, there is evidence indicating sexual dimorphism in response to melatonin on reproductive organs [2,24], In the present study the effects of changes in photoperi ods were investigated in female Djungarian hamsters. In particular, comparisons of the diurnal profiles of melato nin synthesis as well as the profiles of its main precursor, serotonin, and 5-hydroxyindole acetic acid (5-HIAA), a metabolite of serotonin, were studied.…”
Section: -| a C Y C Licmentioning
confidence: 99%